Reliability of Image Capture Technique for the Measurement of Upper Limb Active Joint Position Sense in Healthy Adults - Elnaz Allahverdloo; Iraj Abdollahi (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: Proprioception is the conscious perception of limb position, motion, balance, and pressure. It has a vital role in movement control, especially motor planning and neuromuscular feedback mechanism. To investigate the proprioceptive function, it is essential to use the best measurement method. Different techniques and approaches have been introduced, which are usually expensive and not applicable for clinical use. One of these methods is the image capture technique which is easy and practical. Stillman introduced this technique to measure the joint position sense of the knee considering all variables affecting it and reported its good reliability. Many studies have used this technique for knee and lower limb joints and reported its good reliability, while few studies have used this technique for the upper limb joints. Therefore, this study investigates the reliability of the image capture technique for measuring the Active Joint Position Sense (AJPS) of the left shoulder and elbow in healthy adults. If it yields a good result, it can be used as an available and cost-effective method by clinicians. Materials & Methods: In this methodological study, the participants were 10 healthy adults (5 men, 5 women) aged 18-40 years. To assess the AJPS, we used image capture technology which is one of the most reliable methods for the lower limb joint position sense measurement. Markers were attached on elbow and shoulder landmarks, and photos were taken during the reproduction of angles by participants. Then, the photos were entered into AutoCAD software, and the angles were calculated by drawing line segments from landmarks and connecting them. The absolute error and relative error (the difference between the initial and reproduced angles) were used to measure accuracy. The AJPS was assessed for internal and external rotation of the shoulder and elbow flexion. The measurements were repeated two hours later to assess intra-day reliability and two days later to assess inter-day reliability. Interclass Correlation Coefficient (ICC) and Standard Error of Measurement (SEM) were used for statistical analysis. Results: The ICC of inter-day reliability of the test for all shoulder and elbow movements in relative and absolute errors was reported as excellent (≥0.92). Intra-day reliability was reported excellent (≥0.90) for elbow flexion, and internal rotation of the shoulder in both relative and absolute errors were excellent (0.94). For external rotation of the shoulder, it was excellent in relative error (0.94) and good in absolute error (0.80). All measurements had absolute reliability based on the SEM results. Conclusion: The image capture technique is a simple, cost-effective, and available method tool for measuring AJPS and proprioception in upper limbs by clinicians and researchers.